Perilesional Inflammation in Neurocysticercosis - Relationship Between Contrast-Enhanced Magnetic Resonance Imaging, Evans Blue Staining and Histopathology in the Pig Model. - Carla Cangalaya; Javier A Bustos; Juan Calcina; Ana Vargas-Calla; Diego Suarez; Armando E Gonzalez; Juan Chacaltana; Cristina Guerra-Giraldez; Siddhartha Mahanty; Theodore E Nash; Hector H García; Cysticercosis Working Group in Peru (PLoS Neglected Tropical Diseases, 2016)
BACKGROUND:Disease manifestations in neurocysticercosis (NCC) are frequently due to inflammation of degenerating Taenia solium brain cysts. Exacerbated inflammation post anthelmintic treatment is associated with leakage of the blood brain barrier (BBB) using Evans blue (EB) staining. How well EB extravasation into the brain correlates with magnetic resonance imaging (MRI) using gadolinium (Gd) enhancement as a contrast agent and pericystic inflammation was analyzed in pigs harboring brain cysts of Taenia solium. METHODOLOGY/PRINCIPAL FINDINGS:Three groups of 4 naturally infected pigs were assessed. The first and second groups were treated with both praziquantel plus albendazole and sacrificed two and five days post treatment, respectively. A third untreated group remained untreated. Pigs were injected with EB two hours prior to evaluation by Gd-enhanced T1-MRI, and euthanized. The EB staining for each cyst capsule was scored (EB grades were 0: 0%; 1: up to 50%; 2: over 50% but less than 100%; 3: 100%). Similarly, the Gd enhancement around each cyst was qualitatively and quantitatively scored from the MRI. The extent of pericystic inflammation on histology was scored in increasing severity as IS1, IS2, IS3 and IS4. Grade 3 EB staining and enhancement was only seen in treated capsules. Also, treated groups had higher Gd intensity than the untreated group. Grades of enhancement correlated significantly with Gd enhancement intensity. EB staining was correlated with Gd enhancement intensity and with IS4 in the treated groups. These correlations were stronger in internally located cysts compared to superficial cysts in treated groups. SIGNIFICANCE:EB staining and Gd enhancement strongly correlate. The intensity of enhancement determined by MRI is a good indication of the degree of inflammation. Similarly, EB staining highly correlates with the degree of inflammation and may be applied to study inflammation in the pig model of NCC.